Current advances in the identification of plant nematode diseases: From lab assays to in-field diagnostics - Shao, Hudie; Zhang, Pan; Peng, Deliang; Huang, Wenkun; Kong, Ling-an; Li, Chuanren; Liu, Enliang; Peng, Huan (Frontiers in Plant Science, 2023)
Plant parasitic nematodes (PPNs) cause an important class of diseases that occur in almost all types of crops, seriously affecting yield and quality and causing great economic losses. Accurate and rapid diagnosis of nematodes is the basis for their control. PPNs often have interspecific overlays and large intraspecific variations in morphology, therefore identification is difficult based on morphological characters alone. Instead, molecular approaches have been developed to complement morphology-based approaches and/or avoid these issues with various degrees of achievement. A large number of PPNs species have been successfully detected by biochemical and molecular techniques. Newly developed isothermal amplification technologies and remote sensing methods have been recently introduced to diagnose PPNs directly in the field. These methods have been useful because they are fast, accurate, and cost-effective, but the use of integrative diagnosis, which combines remote sensing and molecular methods, is more appropriate in the field. In this paper, we review the latest research advances and the status of diagnostic approaches and techniques for PPNs, with the goal of improving PPNs identification and detection.